Analisis Kinerja Keuangan Berdasarkan Rasio Profitabilitas pada Perusahaan Subsektor Transportasi yang Terdaftar di BEI - Muhammad Fikri Ramadhan; Harun Blongkod; Siti Pratiwi Husain (Universitas Batanghari, 2023)
This research was sparked by the large difference in the number of passengers to the percentage of income which can be a threat to declining profits from the transportation subsector. The purpose of this study is to identify and analyze the development of financial performance based on profitability ratios in transportation subsector companies using the trend analysis method in the period before and during the pandemic. This study uses descriptive quantitative research methods with data analysis using trend analysis. The research sample is 9 transportation sector companies listed on the IDX. The results of the study show that before the pandemic, not all companies had good financial performance in terms of profitability ratios, NPM, GPM, ROA, ROE. However, most of the company samples showed a decrease in the level of profitability ratios during the pandemic. So it can be concluded that some of the sample companies were affected by the Covid-19 pandemic.